Nonoperative Management of Perforated Diverticulitis of the Duodenum: Report of Three Cases and Review of Literature. (20th February 2021) - Franken, Rutger; Möllers, Martijn; de Mol van Otterloo, Alexander; Puylaert, Julien
Abstract : Duodenal diverticula are relatively frequent but complications are uncommon. The mortality rate of perforated duodenal diverticulitis is high, and its management is controversial. We report three patients with a perforated duodenal diverticulitis who were successfully treated with conservative antibiotic therapy. The clinical presentation in all three patients was acute onset of pain in the upper abdomen. In all cases, ultrasound showed no abnormalities, but computed tomography revealed the correct diagnosis. All three were treated with broad-spectrum antibiotics and total parenteral nutrition. They recovered clinically and laboratory findings normalized. During follow-up visit, all patients were asymptomatic. This study contributes another three patients to the small number of successful conservatively treated cases of perforated duodenal diverticulitis described in literature. We suggest that in patients in good condition with no septic signs, conservative treatment with close clinical follow-up should be the treatment of choice.